2020
DOI: 10.1038/s41379-020-0591-3
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin to P-cadherin switching in lobular breast cancer with tubular elements

Abstract: Loss of E-cadherin expression due to mutation of the CDH1 gene is a characteristic feature of invasive lobular breast cancer (ILBC). Beta-catenin, which binds to the cytoplasmic domain of E-cadherin, is simultaneously downregulated, reflecting disassembly of adherens junctions (AJs) and loss of cell adhesion. E-cadherin to P-cadherin expression switching can rescue AJs and cell adhesion. However, P-cadherin has not been implicated in ILBC, so far. We aimed to characterize 13 ILBCs with exceptional histomorphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 46 publications
4
63
0
Order By: Relevance
“…Recently, a series of ILC with tubular elements representing the rare tubulo-lobular variant of ILC was investigated. The authors demonstrated the phenomenon of focal cadherin switching, wherein activation of P-cadherin, in an otherwise E-cadherin-negative tumour, rescued the function of the adherens junction enabling tubule formation [65]. Notably, co-incident LCIS did not express P-cadherin.…”
Section: What Is New In Invasive Lobular Carcinoma?mentioning
confidence: 99%
“…Recently, a series of ILC with tubular elements representing the rare tubulo-lobular variant of ILC was investigated. The authors demonstrated the phenomenon of focal cadherin switching, wherein activation of P-cadherin, in an otherwise E-cadherin-negative tumour, rescued the function of the adherens junction enabling tubule formation [65]. Notably, co-incident LCIS did not express P-cadherin.…”
Section: What Is New In Invasive Lobular Carcinoma?mentioning
confidence: 99%
“…BC of NST and ILC share a morphologic overlap. Cases in the morphologic overlap may be interpreted as (i) collision tumors, (ii) NST with lobular-like growth pattern but no loss of cell adhesion, and (iii) ILC with tubular elements [58,59]. For details, see text Section 2.3.…”
Section: Ilc As Carcinoma Growing In Single Filesmentioning
confidence: 99%
“…However, mutations in β-catenin/CTNNB1, which are not uncommon in various cancer entities and in some mesenchymal tumors [96][97][98], are consistently absent in ILC [43,99]. Whatever the mechanism, loss of E-cadherin is observed in 55-100% of cases (Appendix A, Table A2) [9][10][11][12][41][42][43]59,61,82,88,90,. CDH1 mutation, as determined by DNA sequencing, is observed in 12-85% of cases (Appendix A, Table A2).…”
Section: Ilc As a Morpho-molecular Entitymentioning
confidence: 99%
See 2 more Smart Citations